2006
DOI: 10.1002/ad.314
|View full text |Cite
|
Sign up to set email alerts
|

Collective Intelligence in Design

Abstract: That digital technology has transformed the forms and spaces of what we design has become commonplace. Its transformative potential for forms of design practice and spaces of knowledge has remained less examined, but is ultimately more radical in its implications. With the shift from the second machine age to that of information, the reflexive network has replaced the assembly line as a preeminent model of organisation even as media infrastructures have augmented physical transportation at multiple scales stre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 0 publications
1
14
0
1
Order By: Relevance
“…found that intermittent rather than constant social influence produced the best performance among humans collectively engaged in complex problem solving [ 81 ]. As we are reminded in Hight & Perry's article on collective intelligence and architectural design, ‘collective intelligence is not simply technical, but also explicitly social, political, and by extension, professional’ [ 2 , p. 6]. Our findings empirically reinforce their caution that the relationship between architectural design and collective intelligence extends beyond technical considerations.…”
Section: Discussionsupporting
confidence: 75%
See 3 more Smart Citations
“…found that intermittent rather than constant social influence produced the best performance among humans collectively engaged in complex problem solving [ 81 ]. As we are reminded in Hight & Perry's article on collective intelligence and architectural design, ‘collective intelligence is not simply technical, but also explicitly social, political, and by extension, professional’ [ 2 , p. 6]. Our findings empirically reinforce their caution that the relationship between architectural design and collective intelligence extends beyond technical considerations.…”
Section: Discussionsupporting
confidence: 75%
“…This second empirical study was also a quasi-field experiment at a Fortune 500 multinational and was conducted at the global headquarters of OpenCo2. 2 At the time of the study, OpenCo2 was in the process of a multi-year headquarters redesign, which-as in Study 1-involved a transformation from assigned seats in cubicles to similarly assigned seats in an open office design, with large rooms of desks and monitors and no dividers between people's desks.…”
Section: Studymentioning
confidence: 99%
See 2 more Smart Citations
“…Instead, a new capacity for collaboration has encouraged new types of design practice (Hight and Perry 2006). Encouraged by the rise of telecommunication technologies, new 'interconnections' and 'configurations of knowledge' have materialised (Gibbons et al 1994) and presented new opportunities for creative engagement.…”
Section: Introductionmentioning
confidence: 97%